Preparation, structural characterization, antioxidant activity and protection against cisplatin-induced acute kidney injury by polysaccharides from the lateral root of Aconitum carmichaelii - Tian, Maoying; Wang, Lin; Dong, Zhaowei; Wang, Xi; Qin, Xiaoyan; Wang, Chao; Wang, Jin; Huang, Qinwan (Frontiers in Pharmacology, 2022)
Response surface methodology (RSM) and Box- Behnken design (BBD) based on one-way experiments were used to optimize the extraction parameters of the lateral root polysaccharides of Aconitum carmichaelii. The extracted polysaccharides were named as RFP. The optimal conditions included a water to raw material ratio of 43, an extraction time of 2 h, and an extraction temperature of 90°C. The shape of RFP was shown by infrared spectroscopy (IR) and scanning electron microscopy (SEM) analysis. The monosaccharide composition and molecular weight of RFP was determined by high-performance liquid chromatography (HPLC). Furthermore, RFP exhibited moderate antioxidant activity by analyzing the scavenging rates of 2,2-diphenyl-1-picrylhydrazyl radical, superoxide anion radical, hydroxyl radical, and ABTS+ radical. RFP exerted cytoprotective effects against hydrogen peroxide (H2O2)-induced injury in the rat renal tubular epithelial cell line rat renal tubular epithelial cells (NRK-52E) and inhibited apoptosis. In addition, researches found that RFP could alleviate cisplatin-induced acute kidney injury in mice by enhancing the levels of glutathione (GSH) and glutathione peroxidase-4(GPX-4), decreasing the levels of malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE), reducing lipid peroxidation, and thus inhibiting ferroptosis. In conclusion, this study provides a good strategy for obtaining bioactive polysaccharides from Fuzi.